Are Caring, Collaborative and Creative Research Practices Possible in the Western Academy? - Firmin, Caroline; Harman, Kerry; Polonyi, Réka (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2025)
This paper reflects on a set of exploratory feminist research practices used by a cross-disciplinary group of adult education practitioners and academic researchers in a recent Arts and Humanities Research Council funded project in the United Kingdom. The authors, one of whom is a paid homecare worker, consider if caring, collaborative and creative research practices are actually possible in the western academy (at least in the UK) based on their experiences in the current project. They conclude that while there are still significant changes needed that ‘mobilising the feminist imaginary’ from within the academy is one way to begin these experiments in creating moments of equality.